A family of ssa-type copper-based MOFs constructed from unsymmetrical diisophthalates: synthesis, characterization and selective gas adsorption. (21st August 2017) - Chen, Fengli; Bai, Dongjie; Wang, Yao; Jiang, Donghao; He, Yabing
Abstract : Three unsymmetrical diisophthalate ligands were used for the first time to construct novel copper-based MOFs exhibiting promising potential for C2 H2 storage and separation as well as natural gas purification. Abstract : In this work, three porous MOFs (ZJNU-74, ZJNU-75 andZJNU-76 ) were constructed via solvothermal reactions of unsymmetrical naphthalene-derived diisophthalate ligands and Cu 2+ ions. As revealed by single-crystal X-ray diffraction analyses, they consist of dicopper [Cu2 (COO)4 ] paddlewheels connected by the organic ligands to form three-dimensional networks with the samessa topology, thus representing a MOF platform which allows understanding of the structure–property relationship. The gas adsorption properties of the three MOF compounds with respect to C2 H2, CO2 and CH4 have been systematically investigated. They exhibit very high C2 H2 uptakes varying from 179.2 to 188.6 cm 3 (STP) g −1 and CO2 uptakes varying from 88.1 to 99.2 cm 3 (STP) g −1 at 298 K and 1 atm. The predicted IAST selectivities range from 24.9 to 29.7 for an equimolar C2 H2 /CH4 gas mixture and from 4.8 to 5.4 for an equimolar CO2 /CH4 gas mixture at 298 K and 1 atm. These results reveal that they possess very promising potential for C2 H2 /CH4 and CO2 /CH4 separations. In particular, compared to the unmodified parent MOFZJNU-74, the alkoxy group-functionalized MOFsZJNU-75 andZJNU-76 exhibit comparable and even higher C2 H2 and CO2 uptake capacities as well as better C2 H2 /CH4 and CO2 /CH4 adsorption selectivities under ambient conditions, which might be attributed to the optimized pore sizes as a result of ligand modification.